Utilization of Augmented Reality in Architecture Pedagogy with A Case Study of Lego House Denmark - Vania Azalia Audrey Lesmana; Kelly Lim; Brigitha Watuseke (Journal of Artificial Intelligence in Architecture, 2025)
This study explores the utilisation of Augmented Reality (AR) in architectural education through a case study of LEGO House. AR offers an innovative approach by integrating traditional design methods with digital technology to enhance students' understanding of design exploration. The research methodology includes a literature review, bibliometric analysis, and data collection through questionnaires assessing architecture students' experiences with AR. The main findings indicate that integrating AR with physical models such as LEGO enhances design visualisation efficiency and student engagement in the learning process. Specifically, 96.2% of respondents agreed that digital technology improves design accuracy and efficiency, while 88.5% emphasised the importance of physical models in understanding proportions and scale. These findings align with existing literature, highlighting AR's role in bridging traditional and digital design methodologies. The implications of this research contribute to the development of more innovative teaching methods in architectural education and suggest further exploration of AR's long-term impact on design learning.